2008
DOI: 10.1016/j.ijimpeng.2007.07.006
|View full text |Cite
|
Sign up to set email alerts
|

On the dynamic fragmentation of two limestones using edge-on impact tests

Abstract: Two limestones are studied to compare the fragmentation pattern induced by dynamic loads. A quasi-static characterization allows one to determine the basic mechanical properties and to compare the two rocks in terms of Weibull parameters, indicators of microstructural differences. Edge-on impacts are performed and show the important role of the Weibull modulus in the fragmentation pattern. Simulations of these experiments are performed and validate the simple model proposed for rocks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 40 publications
(50 reference statements)
0
31
0
Order By: Relevance
“…To study the kinetic of damage at a laboratory scale, EOI tests were developed by the Ernst-Mach-Institute (EMI) in Germany (Hornemann et al 1984;Strassburger and Senf 1994) and in Centre Technique d'Arcueil in France (Riou 1996;Denoual 1998;Forquin 2003). These experiments are particularly adapted to analyze the dynamic fragmentation in brittle materials such as glass (Hornemann et al 1984;Brajer et al 2003), ceramics (Strassburger and Senf 1994;Riou et al 1998;Denoual and Hild 2000;Forquin et al 2003), rocks (Grange et al 2008) or high-strength concretes Forquin and Hild 2008). In open configuration, the fragmentation process may be observed as function of time by using a high speed camera.…”
Section: Edge-on Impact Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…To study the kinetic of damage at a laboratory scale, EOI tests were developed by the Ernst-Mach-Institute (EMI) in Germany (Hornemann et al 1984;Strassburger and Senf 1994) and in Centre Technique d'Arcueil in France (Riou 1996;Denoual 1998;Forquin 2003). These experiments are particularly adapted to analyze the dynamic fragmentation in brittle materials such as glass (Hornemann et al 1984;Brajer et al 2003), ceramics (Strassburger and Senf 1994;Riou et al 1998;Denoual and Hild 2000;Forquin et al 2003), rocks (Grange et al 2008) or high-strength concretes Forquin and Hild 2008). In open configuration, the fragmentation process may be observed as function of time by using a high speed camera.…”
Section: Edge-on Impact Testsmentioning
confidence: 99%
“…When a concrete target is subjected to impact, a multiple fragmentation composed of numerous oriented cracks may occur due to tensile hoop stresses at high strain-rates (Riou et al 1998;Forquin et al 2003Grange et al 2008;Forquin andHild 2008, 2009). This phenomenon may be numerically described by constitutive relations to evaluate the level of damage within the core of impacted structures.…”
Section: Modelling Of Dynamic Fragmentation Of Mb50 In Edge-on Impactmentioning
confidence: 99%
“…The EOI technique has been widely used to investigate the damage modes produced by impact loadings of ceramic materials [12,46,47], ultra-high-strength concrete [48] and rocks [3,15,49]. An ultra-high-speed camera is used in the so-called open experimental configuration to observe the growth of damage at recording frequencies of approximately 1 Mfps (million frames per second).…”
Section: Experimental Techniques Devoted To Brittle Materialsmentioning
confidence: 99%
“…10 since only mode I cracks are explicitly described in the present model. However, it was shown that as a first approximation this type model is able to account for confined damage in rocks (Grange et al 2008).…”
Section: Edge-on Impactmentioning
confidence: 99%